Efeito dos tamanhos padronizados de retalhos de madeira na melhoria do funcionamento de um gaseificador de biomassa - Silva, Fernanda de Souza (2017)
The main objective of this paper is to point out the theoretical and experimental aspects of an equipment that produces electrical energy from the gasification of residual biomass. In fact, this approach focuses on the impact produced by the size of the biomass used to feed the gasifier, on its functional performance and consequently on the system as a whole (gasifier/Otto cycle engine/generator). The gasifier used in this work is a co-current downdraft gasifier. The poor gas there produced, feeds an Otto cycle engine, originally fed with gasoline, but has been modified to run on poor gas produced. This engine is coupled to a Toyama generator. Four different sizes of biomass, in the shape of cubes, were used with an edge approximately 13 mm, 16 mm, 20 mm and 27 mm. Among the sizes tested, the one with the edge of 27 mm resulted in lower consumption and better energy efficiency, translated into higher PCI and higher system efficiency (10.59%) when it generated 2.16 kW of electrical power. This result confirms that the use of biomass gasifiers constitutes an excellent alternative to fossil fuels when it comes to the generation of electrical energy, besides being an ecologically correct system.